Absent Ductus Venosus Associated with Partial Liver Defect. (13th June 2018) - Horie, Kenji; Takahashi, Hironori; Matsubara, Daisuke; Kataoka, Koichi; Furukawa, Rieko; Baba, Yosuke; Ohkuchi, Akihide; Matsubara, Shigeki
Abstract : Absent ductus venosus (ADV) is a rare vascular anomaly. We describe a fetus/neonate with ADV with a partial liver defect. A 41-year-old woman was referred to our institute because of fetal cardiomegaly detected by routine prenatal ultrasound, which revealed absence of ductus venosus with an umbilical vein directly draining into the right atrium, consistent with extrahepatic drainage type of ADV. She vaginally gave birth to a 3, 096-gram male infant at 38 weeks of gestation. Detailed ultrasound examination revealed a defect of the hepatic rectangular leaf at half a month postnatally. He showed normal development at 1.5 years of age with the liver abnormality and a Morgagni hernia. Liver morphological abnormality should also be considered as a complication of ADV.